The ways to deal with psychosis in view of Quran and narratives - Hosein Khakpour; Marzie Ravagh; Islam Salari; Abbas GHorbanzade (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Psychosis is a mental illness that causes personality disorders, and is not specific to particular age, but it is possible at all ages in various forms. Given the importance of mental health in the balance of personality, this issue is considered in Islam. So that all acts of worship is scheduled to play the most important role in mental health of humans. The purpose of the present paper is to present the practical methods, to the treatment of psychosis, using religious resources. This study was done in the descriptive and analytical method and in Quran -Narrative view. In addition to say that in the Islamic sources both internal factors such as: Anxiety, loss of identity and ... and external factors such as: Poverty and family disputes make this event. Concluded that: Religious texts Offer four aspects for this problem: A) Insight: Through Unity therapy, Resurrection Health and anthropological. B) Naturally: Through health trust, repentance and virtue medical treatment. C) Motivational: dominate the motivations and emotions D) Active: Through: meditation therapy, physical therapy, occupational therapy and recreational therapy Keywords: Psychosis, Quran, Spiritual health For downloading the full-text of this article please click here.